Enigma ebook - Milligan, Peter (Enigma (1993)., 2021)
Enigma is a visceral, post-modern tale of self-discovery and sexual identity told against the backdrop of outrageous superheroes and villains.Michael Smith lives a meaningless life of routine and boredom. But when the weird characters from Enigma - his favorite childhood comic book hero - seem to come to life, Michael embarks upon an increasingly obsessive crusade to uncover the incredible secret behind their improbable existence. Teaming up with Enigma's comic creator, Smith encounters an insanity-inducing psychopath, a brain-eating serial killer, a suicide-inciting Truthsayer and a teleporting model ""who really sends you"" as his quest uncovers shock-ing truths about his idol... and ultimately himself. With a brand-new cover by Duncan Fegredo and a treasure trove of nearly 50 pages of extras including development art, color sketches, and behind the scenes notes into the making of this celebrated, groundbreaking story.""Beautiful. Literary. Decades ahead of its time. This is the greatest adult superhero comic of the nineties. At least.""–Kieron Gillen The Wicked and the Divine